Perbandingan Produksi Semangka Hibrida (F1) Hasil Silang Tunggal (Single Cross) - Ramdani Ramadani; Anung Wahyudi (Jurnal Penelitian Pertanian Terapan, 2025)
Watermelon (Citrullus lanatus) is a horticultural plant included in the Cucurbitaceae family. The need for watermelon production in Lampung Province in the last three years has increased.Efforts to increase these needs by using superior hybrid seeds. The hybridization stage aims to assemble superior seeds, using the single cross method.The results of the two crosses will produce hybrid plants.The purpose of this study was to test the yield of six single-cross hybrid watermelon strains compared with four commercial variety.The materials used were six hybrid watermelon genotypes and four hybrid kontrol genotypes (F1) as a comparison.The design used was a one-factor Randomized Block Design (RBD), namely hybrid watermelon genotypes, repeated twice to get 20 experimental units.In the F-test analysis there was a real difference then continued with the Least Significant Difference (LSD) test at the 5% level.The observation of quantitative variables has significantly different results for each parameter. The results of the ten genotypes tested had significant differences. Genotype WM 2210-1606 and WM 2210-0806 had results that were not significantly different when compared to the four control genotypes, both from quantitative and qualitative variables.The advantages of WM 2210-1606 that were not significantly different from the comparator genotypes were fruit length, fruit width, fruit weight, fruit skin thickness, and fruit flesh thickness.The advantages of WM 2210-1606 which are significantly different are the level of sweetness of the edge, the harvest age is earlier, and the characteristic oval shape with bright green skin with thick striations. The data from this study can be used as research data and data to be used in the process of registering of watermelon plant varieties (F1).